Quality and safety of care: Moroccan experience - Sara Meziane; Youness Chbab; Mohammed Taous; Brahim Bourkhiss (AOSIS, 2023)
Background. The Ministry of Health and Social Protection (MOHSP) of the Moroccan Kingdom acknowledges the crucial need to improve the quality and safety of care provided to patients. As a result, they have launched a process that involves, developing a conceptual framework and implementing national health policies aimed to enhance services offered to hospital users. Objective. The aim of this study is to identify all the approaches developed by the MOHSP since 1990 to enhance the quality and safety of care. Materials and Methods. This study is a descriptive qualitative analysis. The data was collected over a six-month period, through semi-structured interviews with professionals reporting to the MOHSP, and through a document analysis. Results. The results provide a comprehensive description of approaches to quality and safety of care in the Moroccan health system, the findings reveal that these approaches are based on three complementary strategies: continuous quality improvement, standardization, and safety of care. Conclusions. The Moroccan health system has implemented various strategies to improve the quality and safety of care. However, these strategies have not been sustained due to several factors. To ensure sustainability, the system needs to invest in capital and resources, involve quality experts in hospitals, use processbased approaches, strengthen legislation and regulations related to quality of care, and translate them into implementing decrees.